N-acetylcysteine suppresses LPS-induced pathological angiogenesis - Zhang, Ping; Chu, Chang; Zeng, Shufei; Hocher, Berthold (Cellular physiology and biochemistry, 2018)
Background/Aims: Angiogenesis is a key feature during embryo development but is also part of the pathogenesis of cancer in adult life. Angiogenesis might be modulated by inflammation. Methods: We established an angiogenesis model in chick chorioallantoic membrane (CAM) induced by the exposure of lipopolysaccharide (LPS), and analyzed the effects of the antioxidant N-acetylcysteine (NAC) on angiogenesis in this model as well as on the expression of key genes known to involved in the regulation of angiogenesis. Results: Treatment with NAC was able to normalize LPS induced angiogenesis and restore the LPS-induced damage of vascular epithelium in chick CAM. Using quantitative PCR, we showed that NAC administration normalized the LPS induced expression of Keap1-Nrf2 signaling and oxidative stress key enzyme gene expressions (SOD, GPx and YAP1). Conclusion: We established a LPS-induced angiogenesis model in chick CAM. NAC administration could effectively inhibit LPS-induced angiogenesis and restore the integrity of endothelium on chick CAM. LPS exposure caused an increased expression of genes involved in oxidative stress in chick CAM. NAC administration could abolish this effect.
Gesehen am 19.02.2021